(untitled) (Research, Society and Development, 2020)
Pectin is a polysaccharide that can be applied to various food industry products to modify the viscosity of food. The objective of this work was to optimize the extraction of pectin of jabuticaba peel by modificating the yield, galacturonic acid content (AUA), esterification content (DE), pectin content (P), and neutral sugars (N). The experiment was performed using the technique of factorial planning of complete experiments and surface response analysis. The extraction can be reported through factorial planning with coefficients of determination (R²) of 0.92, 0.91, 0.89, 0.88 and 0.90 for the yield extraction, AUA, DE, P, and N, respectively. The content of AUA ranged from 22.82 to 65.35%, the DE varied from 26.72 to 77.50%, the percentage of P found in the extraction 25.50 to 66.12%. The best performance was verified utilizing the following parameters: extraction time less than 75 min, temperature of 70°C, and citric acid concentration of 0.75 mol.L-1.